Ethoveterinary: traditional medicine in treating mastitis – a review - Mustafa, Suhaili; Mohd Shah, Umi Shafiqah (IAR Consortium, 2020)
Ethnoveterinary medicine is considered a sub- field of ethnobotany that deals with the study of traditional medicines. Ethnoveterinary practices concern to animal healthcare is as old as the domestication of various livestock species. They comprise belief, knowledge, practices, and skills pertaining to healthcare and management of livestock. It serves as an alternative method to treat and prevent various diseases in livestock. The plant has shown to exhibit antibacterial, antifungal, insecticidal and antioxidant activity. Without being treated this infection can lead to major economic lost in diary industry. Thus, this review will summarize on the different medicinal plant varieties commonly used to treat mastitis, bacterial infection on the mammary gland and udder tissue of cattle.